Effect of irrigation and fertilization on the hardening of forest seedlings with potential use for dry tropical forest restoration - Lanuza-Lanuza, Oscar Rafael (2021)
Seedling quality is a key factor influencing growth and survival after transplantation, but few studies have evaluated the effect of cultural practices on the quality of seedlings of broadleaf species natives of the tropical dry forest. In this study, we evaluated the effect of irrigation and fertilization on the quality of forest seedlings with potential use for   tropical dry forests restoration. A completely randomized design was used to test the effect of two intensities of irrigation and fertilization on the quality of seedlings of Swietenia humilis Zucc, Cedrela odorata L. (both Meliaceae) and Ceiba Pentandra, C.F. Gaertn (Malvaceae) during 75 days in the nursery. The Dickson seedling quality index was significantly different between species because of irrigation (P < 0.05). The root mass fraction differed between species because of the additional fertilization (P < 0.05). Slenderness also differed between species depending on irrigation (P < 0.0001) and fertilization (P < 0.05). The application of additional nutrients significantly increased the diameter of the root neck in the three species (P < 0.05) and the ratio of dry root biomass and area (P < 0.05). The height of the seedlings and the total dry weight of the seedlings was higher with additional nutrients and constant irrigation (P < 0.05) and (P < 0.05), respectively. Our data indicate that the seedlings obtained are of high quality and could guarantee greater post-transplant survival.